A Review on Therapeutic Management of Chronic Hepatitis B Infection - Mugilan Poongkunran; Asad Javaid (Archives of Clinical Gastroenterology - Peertechz Publications, 2015)
The current therapeutic goal in the management of chronic hepatitis B (CHB) infection is to persistently suppress hepatitis B virus (HBV) replication and prevent its progression to liver failure and the development of hepatocellular carcinoma (HCC). At present, the therapeutic strategies for CHB includes either a short course of pegylated-interferon-alfa (PEG-IFNa) and/or a long term course of nucleos(t)ide analogues (NA's). NA's are more preferable to PEG-IFNa, majorly for its easier route of administration and excellent tolerance and safety profiles. Entecavir (ETV) and tenofovir (TDF) are the current first line options for its potency to maintain sustained virological response (SVR) in almost 100% of the adherent individuals along with minimal to no long-term resistance. These sustained inhibitions of HBV replication have been shown to be associated with histological improvement, modifying the long-term outcomes. However, HBsAg seroconversion, the best surrogate marker for viral clearance is still unachievable with the current first line agents and hence the risk for hepatocellular carcinoma (HCC) still exists among them. This makes us to still consider, a finite duration of PEG-IFNa that has shown considerable results with regards to HBsAg loss, as an attractive add-on or monotherapy option despite its adverse events profile. Existing evidences do not recommends its usage. However, numerous studies are ongoing and also further studies to evaluate the reliable baseline predictors of response to PEG-IFNa and early on-treatment stopping rules based on age, alanine aminotransferase levels (ALT), HBV DNA levels and HBsAg kinetics would be ideal.